Wild rodents in three provinces of China exhibit a wide range of Enterocytozoon bieneusi diversity - Gao, Zhen-Qiu; Wang, Hai-Tao; Hou, Qing-Yu; Qin, Ya; Qin, Si-Yuan; Zhao, Quan; Ma, He (Frontiers in Veterinary Science, 2024)
IntroductionEnterocytozoon bieneusi is one of the most important zoonotic pathogens, responsible for nearly 90% of human infections. Its host spectrum is broad in China, encompassing humans, non-human primates, domestic animals, wildlife, and wastewater. Wild rodents have the potential to act as carriers of E. bieneusi, facilitating the parasite’s transmission to humans and domestic animals.MethodsThe present study involved the collection of 344 wild rodents, representing nine species, from three provinces in China. The prevalence and genotypes of E. bieneusi were determined through amplification of the ITS gene. Evolutionary analysis was conducted using Mega 5.0 with the neighbor-joining method (Kimura 2-parameter model, 1,000 replicates).ResultsAmong the sampled wild rodents, 41 (11.92%) were tested positive for E. bieneusi. Rattus flavipectus exhibited the highest prevalence (11/39), while Bandicota indica and Rattus rattus sladeni showed no infections (0/39 and 0/5, respectively), highlighting significant differences. Environmental factors strongly influenced E. bieneusi infection; rodents residing in lake beaches (10.27%, 15/146) and fields (19.95%, 18/95) were more susceptible compared to those in mountainous areas (7.77%, 8/103). The study identified four known genotypes (D, Type IV, SDD5, PigEBITS7) and five novel genotypes (HNRV-1 to HNRV-3, GXRL-1, GXRL-2) in the investigated wild rodents, with Genotype D exhibiting the highest prevalence.DiscussionRemarkably, this study reports the presence of E. bieneusi, R. flavipectus, M. fortis, A. agrarius, R. losea, and N. lotipes for the first time. These findings underscore the common occurrence of E. bieneusi infection in wild rodents in China, highlighting its diverse nature and significant potential for zoonotic transmission. Hence, it is imperative to conduct a comprehensive epidemiological investigation of rodent infection with E. bieneusi, particularly focusing on wild rodents that are closely associated with humans. Additionally, developing appropriate measures and monitoring strategies to minimize the risk of infection is essential.